Proteomic Analysis of Human Scleroderma Fibroblasts Response to Transforming Growth Factor‐ß. Issue 4 (6th September 2018) - Chaigne, Benjamin; Clary, Guilhem; Le Gall, Morgane; Dumoitier, Nicolas; Fernandez, Claire; Lofek, Sebastien; Chafey, Philippe; Moinzadeh, Pia; Krieg, Thomas; Denton, Christopher P.; Mouthon, Luc
Abstract : Purpose: Systemic sclerosis (SSc) is characterized by autoimmunity, vasculopathy and fibrosis. Fibrosis is due to an activation of fibroblasts by the transforming growth factor‐ß (TGF‐ß). This study investigates the proteomic response of SSc fibroblasts to TGF‐ß. Experimental design: Skin fibroblasts from diffuse SSc patients and healthy controls (HC) are cultured with or without TGF‐ß. Two‐dimensional differential in‐gel electrophoresis and mass spectrometry (MS) combined with Ingenuity Pathway analysis (IPA) and Panther/David software analyze proteins differentially expressed between groups. Real‐time cell analyzer (RTCA) assesses fibroblast proliferation and viability. Results: Two‐hundred‐and‐seventy‐nine proteins are differentially expressed between groups. Principal component analysis shows significant differences between groups. IPA shows specific process networks such as actin cytoskeleton and integrin signaling. Panther and David software show predominant biological processes such as cellular and metabolic processes. TGF‐ß enhances protein synthesis and protein pathways. IPA and RTCA suggest the involvement of epidermal growth factor receptor (EGFR) and phosphatidylinositol 3 kinase (Pi3K). Conclusions and clinical relevance: That the proteome of fibroblasts differs between SSc patients and HC is confirmed, and it is demonstrated that fibroblasts exacerbate their proteomic phenotype upon stimulation with TGF‐ß. EGFR and Pi3K are highlighted as proteins of interest in SSc fibroblasts.